Hyltech (Hybrid Cultivation Technology) Renewable EnergyBased Shrimp Cultivation Innovation as an Environmentally Friendly Technology to Increase the Economic Welfare of Shrimp Farmers in the Yogyakarta Coastal Area - Ma'ruf, Khakam; Khosyiati , Nur Evirda (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2022)
Indonesia is the largest archipelagic country, almost 75% of its territory is coastal, waters and oceans. The southern coastal area of ​​Kulon Progo Regency, Yogyakarta is the center of fishery economic growth, with a shrimp pond area of ​​more than 150 Ha. The type of shrimp that is widely developed in the area and the superior type is the vannamei shrimp. The application of technology to the shrimp pond oxygen supply system still uses oil-fueled (BBM) technology or engines. The use of fuel causes various problems such as the removal of subsidies which causes fuel prices to rise and environmental pollution of cultivation. Based on these problems, the author offers innovation in shrimp pond aerators with a paper entitled Hyltech (Hybrid Cultivation Technology). The method of writing papers uses data and information collected by literature study methods from print media and journals.